Transmisi Budaya dalam Tradisi Nganggung untuk Pembentukan Karakter Anak Usia Dini di PAUD Kota Pangkalpinang - Nurul Qomariah; Dody Irawan; Yulia (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The nganggung tradition has a very important role in cultural transmission and character formation in early childhood in Pangkalpinang City. By utilizing this tradition as an educational tool, PAUD can contribute to the preservation of local culture while forming a generation that has strong character and is based on cultural values. This research aims to analyze the role of the nganggung tradition as a medium for cultural transmission in character building in early childhood in Pangkalpinang City PAUD. Through a qualitative approach, this research explores the transmission of culture in the nganggung tradition in PAUD Pangkalpinang City. The results of the research show that the transmission process is carried out through imitation of the nganggung tradition in society, although it is not completely the same. Meanwhile, the transmission method is carried out by participating in the implementation of this tradition, although their involvement still requires guidance. The elements transmitted in the nganggung tradition are social values ​​in the life of the Melayu people of Bangka. PAUD institutions as a means of cultural transmission have attempted to pass on the cultural legacy to the nation's new generations so that community traditions do not become extinct.